A matrix of meanings : finding God in pop culture - Detweiler, Craig, 1964-; Taylor, Barry, 1951- (Grand Rapids, Mich. : Baker Academic, 2003)
Ross and Rachel had a baby, Britney and Justin broke up, and Time asked if Bono could save the world. From the glittering tinsel of Hollywood to the advertising slogan you can't get out of your head, we are surrounded by popular culture. In contrast to some traditional Christian responses, which have been to shun aspects of popular culture, Craig Detweiler and Barry Taylor offer an insightful treatise on its value. Rather than offering a theology for pop culture, as some recent commentators have, the authors create a constructive theology out of pop culture. Instead of passing judgment on popular culture the authors analyze its elements and ask "What are they doing?" "What do they represent?" and "What do they say about the world in which we live?" Rather than deciding whether Bono, Britney, and the cast of Friends deserve our admiration, Detweiler and Taylor ask what the phenomena of celebrity idolization means. They do not examine whether Nike's "Just do it" campaign is morally questionable; instead, they ask what its success says about our society.
Introduction : Postmodernity in the marketplace -- Methodology : a matrix of meanings -- Advertising : the air that we breathe -- Celebrities : ancient and future saints -- Music : Al Green makes us cry -- Movies : look closer -- Television : our constant companion -- Fashion : dressing up the soul -- Sports : board generation -- Art : sharks, pills, and ashtrays.
Includes bibliographical references (p. 341-342) and index.
Keywords: Popular culture -- Religious aspects -- Christianity; Popular culture -- United States